2006
DOI: 10.1080/15572536.2006.11832622
|View full text |Cite
|
Sign up to set email alerts
|

Hymenochaetales: a molecular phylogeny for the hymenochaetoid clade

Abstract: The hymenochaetoid clade is dominated by wood-decaying species previously classified in the artificial families Corticiaceae, Polyporaceae and Stereaceae. The majority of these species cause a white rot. The polypore Bridgeoporus and several corticicoid species with inconspicuous basidiomata live in association with brown-rotted wood, but their nutritional strategy is not known. Mycorrhizal habit is reported for Coltricia perennis but needs confirmttion. A surprising element in the hymenochaetoid clade is a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 29 publications
2
78
0
6
Order By: Relevance
“…Wagner and Fischer (2002) confirmed Fulvifomes as an independent genus in Hymenochaetaceae based on nuclear-encoded large subunit rRNA gene (nLSU) sequences. Larsson et al (2006) acknowledged that Fulvifomes was closely related to a clade hosting Aurificaria luteoumbrina (Romell) D.A. Reid and Inonotus porrectus Murrill with phylogenetic evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Wagner and Fischer (2002) confirmed Fulvifomes as an independent genus in Hymenochaetaceae based on nuclear-encoded large subunit rRNA gene (nLSU) sequences. Larsson et al (2006) acknowledged that Fulvifomes was closely related to a clade hosting Aurificaria luteoumbrina (Romell) D.A. Reid and Inonotus porrectus Murrill with phylogenetic evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Members of this clade are almost exclusively wood-decaying white rot fungi and confirmed brown rot fungi are not present, but a few cases of ectomycorrhizal symbionts have been reported (31). Decay activity is usually described as mostly saprotrophic, but some species, notably Porodaedalea pini and Phellinus igniarius, qualify as timber pathogens (31). Two Phellinus species demonstrably decolorize textile dyes, a trait commonly attributed to phenoloxidase activity, but the actual enzymes involved have not been identified (1,45).…”
mentioning
confidence: 99%
“…The Hymenochaetales are a major order of the Agaricomycotina situated in a more basal position than the Polyporales and Agaricales (23). Members of this clade are almost exclusively wood-decaying white rot fungi and confirmed brown rot fungi are not present, but a few cases of ectomycorrhizal symbionts have been reported (31). Decay activity is usually described as mostly saprotrophic, but some species, notably Porodaedalea pini and Phellinus igniarius, qualify as timber pathogens (31).…”
mentioning
confidence: 99%
“…& Hjortstam, Corticiaceae North Europe 6: 1271. First published as a Mycoacia species (Eriksson 1949), Larsson et al (2006) showed with nLSU rRNA gene sequence data that R. pinicola is a member of the Resinicium s.l. clade.…”
Section: Resinicium Rimulosummentioning
confidence: 99%
“…Previous phylogenetic studies employing the large subunit ribosomal RNA (nLSU rRNA) gene sequences placed R. bicolor and related taxa in the hymenochaetoid clade (Hibbett and Binder 2002;Binder et al 2005;Larsson et al 2004Larsson et al , 2006. To confirm their placement in the hymeno chaetoid clade, the nSSU rRNA genes of nine Resinicium and allied taxa were sequenced.…”
Section: And Budingmentioning
confidence: 99%